Analysing teaching reading comprehension strategies for secondary school students: a case study of a rural school in Sri Aman District, Sarawak / Mavis Anak Valentine Jihir - Valentine Jihir, Mavis (2015)
The purpose of this study was to identify the reading strategies used by average proficiency Form Three students in Sekolah Menengah Kebangsaan Sri Aman, Sarawak before and after a strategy instruction. It also aims to investigate whether explicit strategy instruction has an effect on the students' performance in answering reading comprehension tests. 33 students were selected for the purpose of data collection. Questionnaire as well as pretest and posttest were utilized as data collection techniques. Most students were still very weak in the language with the largest number of students scored Grade E in the diagnostic test. They were not actively engaged with the text in a meaningful way. The three research questions involved were: i) what are the reading strategies used by average proficiency Form three students in SMK Sri Aman, Sarawak before the strategy instruction? ii) what are the reading strategies used by average proficiency Form three students in SMK Sri Aman, Sarawak after the strategy instruction? iii) does strategy instruction significantly enhance average proficiency Form three students in SMK Sri Aman, Sarawak in answering reading comprehension questions? The findings of the survey reading strategies from the questionnaire for both before and after the strategy instruction were consistent. There is a slight improvement of the reading comprehension tests before and after the strategy instruction.